Water-based damping coating and preparation method thereof
By performing end group and nanocomposite modification of polyurethane, combined with hindered phenol/epoxy microspheres and montmorillonite emulsion technology, the problems of insufficient damping performance and narrow temperature range of water-based damping coatings are solved, and the damping performance and temperature range are significantly improved. , enhances the material's vibration absorption and noise reduction capabilities.
Patent Information
- Application Number
- CN202411588521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-13
AI Technical Summary
The insufficient damping performance and narrow effective damping temperature range of water-based damping coatings limit their wide application.
By end-group modification and nanocomposite modification of polyurethane, amino and nanomaterials are introduced to increase hardness and cross-link density; hindered phenol/epoxy microspheres are introduced to construct the interfacial hydrogen bond between polyurethane and microspheres, and the damping is improved Performance, and control the microsphere particle size through montmorillonite emulsion curing to broaden the damping temperature range.
It significantly improves the damping performance and mechanical properties of water-based damping coatings, broadens the damping temperature range, and enhances the material's vibration absorption and noise reduction capabilities.
Smart Images

Figure CN119119850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a water-based damping coating and a preparation method thereof. Background Art
[0002] Damping materials are a type of functional materials that absorb or dissipate external energy and play a role in shock absorption, noise reduction, and sound absorption. The wide application of damping materials can reduce the harm caused by vibration. There are many types of damping materials. Among them, viscoelastic damping materials are considered to have great application prospects due to their superior vibration reduction and noise reduction capabilities.
[0003] Damping coating is a special form of viscoelastic damping material, which is divided into solvent-based and water-based damping coating. Traditional solvent-based damping coating is expensive, the preparation process is complicated, the organic solvents used will pollute the environment, and emit a large amount of volatile organic compounds. In contrast, the dispersion medium of water-based damping coating is water with low volatile organic compound content, and the preparation process is simple and diverse. Therefore, water-based damping coating has a wider range of applications. Although water-based damping coating has been widely used and well developed, there are still some technical defects, such as insufficient damping performance and narrow effective damping temperature range, which limit its further development. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a water-based damping coating and a preparation method thereof. The present invention performs end group modification and nanocomposite modification on polyurethane: the hardness and crosslinking density of polyurethane can be increased by introducing amino groups through modification with amine compounds, and the mechanical properties of the damping coating can be modified; the introduction of modified nanomaterials can form nanocomposites with polyurethane to improve the mechanical properties and damping properties of the coating. These nanomaterials are dispersed in the resin matrix to increase the interface area and enhance the vibration absorption effect.
[0005] At the same time, the polyurethane is modified by introducing hindered phenol / epoxy microspheres. The present invention adopts a method of direct curing of montmorillonite emulsion to prepare hindered phenol / epoxy microspheres, and then introduces hindered phenol into polyurethane by using microspheres, and by enriching hindered phenol on the surface of microspheres, constructing interfacial hydrogen bonds between polyurethane and microspheres, thereby improving the damping performance of the composite material and the compatibility of the microspheres with polyurethane. Epoxy resin, as a second phase polymer, can broaden the damping temperature range of the composite material and improve the sound transmission loss of the composite material. The montmorillonite in the emulsion ensures the controllable particle size of the microspheres. The microspheres can effectively modify the water-based resin and improve the damping performance and noise reduction performance of the composite material. The surface acid etching treatment of the hindered phenol / epoxy microspheres can increase its surface roughness and active sites, thereby improving the damping performance of the composite material.
[0006] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a water-based damping coating, which comprises modified polyurethane, surface acid-etched hindered phenol / epoxy microspheres, fillers, and additives.
[0007] As a preferred technical solution of the present invention, the water-based damping coating comprises the following components in parts by mass: 50-70 parts of modified polyurethane, 10-20 parts of surface acid-etched hindered phenol / epoxy microspheres, 5-15 parts of filler, and 2-10 parts of additives. Wherein, the mass part of modified polyurethane can be 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts or 70 parts, the mass part of surface acid-etched hindered phenol / epoxy microspheres can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, the mass part of filler can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, and the mass part of auxiliary agent can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts. , 5, 6, 7, 8, 9 or 10 parts, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0008] The present invention introduces an amine compound to modify the polyurethane: the chemical structure of the polyurethane generally contains a carbamate bond formed by the reaction of isocyanate and polyol, and the amine compound generally has two or more active amino groups, which can react with the isocyanate group to form a urea bond, thereby forming a highly cross-linked polyurethane network structure. The increase in cross-linking can improve the hardness and elastic modulus of the polyurethane, so that it can better absorb and dissipate energy under stress and enhance the damping performance; at the same time, the urea bond formed has a higher polarity, so that the hydrogen bonds and van der Waals forces between the polyurethane molecules are enhanced, thereby increasing the internal friction between the molecular chains. This increased internal friction helps to improve the damping performance of the material, because the material can dissipate more energy through friction and deformation under stress. In addition, since the urea bond is more stable than the carbamate bond, especially under high temperature conditions, the use of amine compounds for modification can improve the thermal stability of the polyurethane, thereby enhancing its service life and performance in harsh environments.
[0009] At the same time, the present invention introduces nanomaterials into polyurethane for modification: due to its high specific surface, the nanomaterials can provide a large number of interface areas in the polyurethane matrix, which can improve the interface interaction between the matrix and the nanomaterials, thereby increasing the internal friction of the material and further improving the damping performance; at the same time, the introduction of nanomaterials can form dispersed multiphase structures in the polyurethane matrix, which can effectively hinder the expansion of cracks and energy transfer, thereby consuming more mechanical energy. This multiphase structure has a significant effect on the concentrated distribution and consumption of stress, and helps to enhance the damping capacity of the material.
[0010] The use of chitosan to modify nanomaterials can reduce the agglomeration tendency of nanomaterials, thereby improving the processing and dispersion properties of nanomaterials in the polyurethane matrix. This modification helps to improve the uniformity and quality of the composite material, making its performance stable in practical applications. At the same time, chitosan molecules are rich in active amino groups, which can react with isocyanates in the polyurethane matrix, thereby enhancing the interfacial compatibility between the nanomaterials and the polyurethane matrix, helping to improve the dispersion and stability of the material in the polyurethane matrix, thereby enhancing the mechanical properties and damping properties of the composite material.
[0011] The present invention introduces hindered phenol / epoxy microspheres to modify polyurethane. Antioxidant AO-80 is a kind of hindered phenol. The large groups in its macromolecular structure will generate internal friction during the deformation process, further increasing the dissipation of energy, thereby improving the damping performance of the material; by enriching the hindered phenol on the surface of the microspheres, hydrogen bonds between the microspheres and the polyurethane matrix can be constructed. This interfacial bonding can not only enhance the dispersibility of the microspheres in the matrix, but also prevent the microspheres from falling off from the matrix during use, thereby improving the long-term stability of the composite material. Epoxy resin, as the matrix of the microspheres, can form a strong interfacial interaction with the polyurethane matrix. The larger interfacial area between the two can further dissipate energy and enhance the damping effect.
[0012] Epoxy resin has a higher glass transition temperature, while the glass transition temperature of polyurethane is relatively low. By introducing epoxy microspheres, a multiphase composite material with different glass transition temperatures can be formed. This multiphase structure can play a damping role in a wider temperature range, avoiding the material from losing its damping effect at a specific temperature, thereby broadening the effective damping temperature range of the coating.
[0013] Epoxy resin microspheres have high strength and high modulus. As a micron or submicron reinforcement phase, they can effectively improve the mechanical strength and rigidity of the polyurethane matrix. This reinforcement not only helps maintain the structural integrity of the coating, but also improves the durability of the coating under dynamic stress. Hindered phenols themselves have good antioxidant properties, which can stabilize the structure of the microspheres and extend the service life of the coating. The addition of hindered phenols can also prevent the polyurethane matrix from being degraded due to oxidation during long-term use, thereby maintaining the mechanical properties of the coating.
[0014] At the same time, the introduction of microspheres can effectively change the acoustic properties of the coating, reducing noise by scattering and absorbing sound waves. In particular, when the size of the microspheres matches the wavelength of the sound waves, the noise reduction ability of the coating can be significantly enhanced; and the microspheres provide multiple energy dissipation points inside the material, so that the coating can more effectively attenuate the vibration energy when vibrating, thereby improving the vibration reduction performance of the overall material.
[0015] In the preparation of hindered phenol / epoxy microspheres by direct curing of montmorillonite, the introduction of montmorillonite can control the particle size and distribution of hindered phenol / epoxy microspheres. Uniform microsphere size and distribution can ensure the consistency of material properties and avoid stress concentration or performance fluctuations caused by uneven microsphere size or distribution.
[0016] Acid etching of hindered phenol / epoxy microspheres can make their surface rougher. The increase in surface roughness can provide more mechanical interlocking points, thereby enhancing the physical bonding between the microspheres and the polyurethane matrix. Stronger interfacial bonding helps to improve the overall mechanical properties and damping effect of the composite material. Acid etching can increase the hydrophilicity of the microsphere surface, making the microspheres have better dispersibility in the waterborne polyurethane coating system. Its good dispersibility can ensure that the microspheres are evenly distributed in the coating and avoid agglomeration, thereby improving the uniformity and stability of the coating. At the same time, the surface of the microspheres after acid etching contains more active sites, which can form a more complex interface structure with the polyurethane matrix. The complex interface structure will cause greater molecular chain movement and interface friction when the material is subjected to force, thereby enhancing the internal friction and energy dissipation capacity of the material and improving the damping performance. In addition, the rough surface of the microspheres is more likely to produce microscopic deformation when subjected to mechanical stress, further increasing the internal friction and energy absorption capacity of the material. This microscopic deformation can effectively convert external impact energy into heat energy, thereby reducing vibration and noise.
[0017] The present invention limits the mass portion of surface acid-etched hindered phenol / epoxy microspheres to 10 to 20 parts, and an appropriate amount of hindered phenol / epoxy microspheres can significantly improve the damping performance of the coating. The introduction of microspheres can increase the internal friction and energy dissipation path of the material, enhance the energy dissipation capacity of the coating when subjected to vibration or impact, and thus improve the damping effect. If the content of hindered phenol / epoxy microspheres is too high, agglomeration may occur between the microspheres, resulting in weakened interface interaction, reduced microsphere dispersion effect, and thus weakened damping performance; at the same time, too high a microsphere content may cause the material rigidity to increase, reduce the flexibility and internal friction of the coating, and be unfavorable to the damping performance.
[0018] In a second aspect, the present invention provides a method for preparing a water-based damping coating, the preparation method comprising: S1: dispersing emulsifier OP-10 and montmorillonite in deionized water, stirring at a constant temperature to obtain emulsion A; mixing bisphenol A diglycidyl ether and antioxidant AO-80, stirring to obtain a mixed solution A, slowly dripping the mixed solution A into emulsion A, stirring at a constant temperature to obtain emulsion B, then adding meta-phenylenediamine into emulsion B, filtering, washing, and drying after solidification to obtain hindered phenol / epoxy microspheres; preparing an acid solution, dispersing the hindered phenol / epoxy microspheres in the acid solution to obtain dispersion A, stirring, filtering, washing, and drying to obtain surface acid-etched hindered phenol / epoxy microspheres; S2: Mix acetic acid and deionized water to obtain an acetic acid solution, then add chitosan, stir to obtain a chitosan solution, add nanomaterials to the chitosan solution to obtain a dispersion B, react, filter, wash and dry to obtain a modified nanomaterial; dissolve waterborne polyurethane in NN dimethylformamide, stir to obtain a polyurethane solution; dissolve an amine compound in anhydrous ethanol to obtain an amine compound solution, add the amine compound solution to the polyurethane solution, stir to obtain a reaction solution, place the reaction solution in a reflux device for reaction, cool it naturally, add the modified nanomaterial to obtain a mixed solution B, ultrasonicate, stir at a constant temperature to obtain a mixed solution C, add deionized water to the mixed solution C, filter, wash and dry to obtain a modified polyurethane; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water, stir, add fillers and additives during the stirring process, and stir evenly to obtain a water-based damping coating.
[0019] As a preferred technical solution of the present invention, in step S1, the mass ratio of the emulsifier OP-10 to deionized water is 1: (15-25), for example, it can be 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23, 1:24 or 1:25, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In some optional examples, the mass ratio of montmorillonite to deionized water is 1: (20-30), for example, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional embodiments, the stirring temperature of the emulsion A is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional examples, the stirring time of the emulsion A is 1 to 2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional examples, the emulsion A is stirred at a speed of 1000-1500 rpm, for example, 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm or 1500 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional examples, the mass ratio of bisphenol A diglycidyl ether to antioxidant AO-80 is (1~5):1, for example, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] In some optional embodiments, the stirring temperature of the mixed solution A is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional embodiments, the stirring time of the mixed solution A is 1 to 2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional examples, the dropping speed of the mixed solution A when added dropwise to the emulsion A is 1 to 3 g / min, for example, 1 g / min, 1.2 g / min, 1.4 g / min, 1.6 g / min, 1.8 g / min, 2 g / min, 2.2 g / min, 2.4 g / min, 2.6 g / min, 2.8 g / min or 3 g / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional examples, the mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in the emulsion B is 1:(1-2); for example, it can be 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional embodiments, the stirring temperature of the emulsion B is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional examples, the stirring time of the emulsion B is 1 to 2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional examples, the emulsion B is stirred at a speed of 1000-1500 rpm, for example, 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm or 1500 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the feeding amount of meta-phenylenediamine is 2 to 5 g, for example, it can be 2 g, 2.2 g, 2.4 g, 2.6 g, 2.8 g, 3 g, 3.2 g, 3.4 g, 3.6 g, 3.8 g, 4 g, 4.2 g, 4.4 g, 4.6 g, 4.8 g or 5 g, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional examples, the curing temperature of the emulsion B is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the curing time of the emulsion B is 3 to 4 hours, for example, it can be 3 h, 3.1 h, 3.2 h, 3.3 h, 3.4 h, 3.5 h, 3.6 h, 3.7 h, 3.8 h, 3.9 h or 4 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional embodiments, the drying temperature of the hindered phenol / epoxy microspheres is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional embodiments, the drying time of the hindered phenol / epoxy microspheres is 4 to 6 hours, for example, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional examples, the volume fraction of the acid in the acid solution is 10-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional examples, the mass ratio of the hindered phenol / epoxy microspheres to the acid solution is 1:(10-20), for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional embodiments, the stirring temperature of the dispersion A is 25-35°C, for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional embodiments, the stirring time of the dispersion A is 30 to 60 min, for example, it can be 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the drying temperature of the surface acid-etched hindered phenol / epoxy microspheres is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional examples, the drying time of the surface acid-etched hindered phenol / epoxy microspheres is 12 to 24 hours, for example, it can be 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] As a preferred technical solution of the present invention, in step S2, the mass ratio of acetic acid to deionized water is 1:(10-20), for example, it can be 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional examples, the feeding amount of chitosan is 5-15 g / L, for example, it can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L or 15 g / L, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the nanomaterial accounts for 1-5% of the mass of the chitosan solution, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the reaction time of the dispersion B is 1 to 2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the drying temperature of the modified nanomaterial is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional examples, the drying time of the modified nanomaterial is 1 to 2 hours, for example, it can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional examples, the polyurethane accounts for 10-20% of the mass of NN dimethylformamide, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional embodiments, the stirring temperature of the polyurethane solution is 20-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional examples, the polyurethane solution is stirred for 1 to 2 hours, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the amine compound accounts for 5-20% of the mass of the polyurethane, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the reaction temperature of the reaction solution in the reflux device is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the reaction time of the reaction solution in the reflux device is 2 to 4 hours, for example, it can be 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the modified nanomaterial accounts for 1-5% of the mass of the polyurethane, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the power of the ultrasound of the mixed solution B is 200-300 W, for example, 200 W, 210 W, 220 W, 230 W, 240 W, 250 W, 260 W, 270 W, 280 W, 290 W or 300 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the ultrasonic time of the mixed solution B is 10 to 30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional embodiments, the stirring temperature of the mixed solution B is 60-80°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the stirring time of the mixed solution B is 1 to 2 h, for example, 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional embodiments, the drying temperature of the modified polyurethane is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the drying time of the modified polyurethane is 12 to 24 hours, for example, it can be 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] Compared with the prior art, the present invention has the following beneficial effects: (1) The introduction of amino groups increases the hardness and cross-linking density of polyurethane, thereby enhancing the damping performance; the introduction of modified nanomaterials to form a multiphase structure in the polyurethane matrix helps to enhance the damping capacity of the material; (2) Hindered phenol / epoxy microspheres were introduced to modify polyurethane and construct interfacial hydrogen bonds between polyurethane and microspheres, thereby improving the damping properties of the composite material and the compatibility of the microspheres with polyurethane.
[0063] (3) Surface acid etching of hindered phenol / epoxy microspheres can increase their surface roughness and active sites, thereby improving the damping properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 A flow chart of a method for preparing a water-based damping coating provided in Examples 1 to 4 of the present invention; Figure 2 The infrared spectra of the modified polyurethane with and without the addition of surface acid-etched hindered phenol / epoxy microspheres provided in Example 1 of the present invention; Figure 3 The composite loss coefficient curve diagram of the water-based damping coating provided in Examples 1 to 4 and Comparative Examples 1 to 2 of the present invention. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0066] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows: Emulsifier OP-10: purchased from Sinopharm Chemical Reagent Co., Ltd.; Montmorillonite: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Bisphenol A diglycidyl ether: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Antioxidant AO-80: purchased from TCI (Shanghai) Chemical Industry Development Co., Ltd. Meta-phenylenediamine: purchased from Jiangsu Bosite Chemical Technology Co., Ltd.; Sulfuric acid: purchased from Sinopharm Chemical Reagent Co., Ltd.; Nitric acid: purchased from Sinopharm Chemical Reagent Co., Ltd.; Anhydrous ethanol: purchased from Sinopharm Chemical Reagent Co., Ltd.; Acetic acid: purchased from Shanghai Denuo Chemical Co., Ltd.; Chitosan: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Nano-silicon dioxide: purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; Nano calcium carbonate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Nanographene: purchased from Shanghai Myril Biochemical Technology Co., Ltd.; Waterborne polyurethane: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; NN dimethylformamide: purchased from Shanghai Denuo Chemical Co., Ltd.; Ethylenediamine: purchased from Sinopharm Chemical Reagent Co., Ltd.; Diethylenetriamine: purchased from Jinan Liyang Chemical Co., Ltd. Hexamethylenediamine: purchased from Shanghai MacLean Biochemical Technology Co., Ltd. Mica powder: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.; Talc: purchased from Shanghai Yien Chemical Technology Co., Ltd. Aluminum silicate: purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.; Plasticizer: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Defoaming agent: purchased from Nantong Runfeng Petrochemical Co., Ltd. Preservatives: purchased from Jiangsu Xinyu Biotechnology Co., Ltd. Anti-settling agent: purchased from Changxing Xiehe Polymer Materials Co., Ltd.
[0067] Example 1 This embodiment provides a water-based damping coating and a preparation method thereof, wherein the water-based damping coating comprises the following components in parts by weight: 55 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 10 parts; 8 parts of filler; 5 parts of additives.
[0068] like Figure 1 As shown, the preparation method of the water-based damping coating specifically includes the following steps: S1: Disperse emulsifier OP-10 and montmorillonite in deionized water, wherein the mass ratio of emulsifier OP-10 to deionized water is 1:25, and the mass ratio of montmorillonite to deionized water is 1:20, and stir at a temperature of 75°C and a rotation speed of 1000 rpm for 1 hour to obtain emulsion A; mix bisphenol A diglycidyl ether and antioxidant AO-80 in a mass ratio of 1:1, and stir at 120°C for 2 hours to obtain a mixed solution A, and slowly drip the mixed solution A into the emulsion A at a dropping speed of 1 g / min, and stir at a temperature of 65°C and a rotation speed of 1500 rpm for 2 hours to obtain emulsion B, The mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in emulsion B is 1:1, and then 2g of meta-phenylenediamine is added to emulsion B, and after curing at 70°C for 4 hours, the hindered phenol / epoxy microspheres are filtered, washed, and dried to obtain hindered phenol / epoxy microspheres, wherein the drying temperature is 60°C and the time is 4 hours; a sulfuric acid solution with a volume fraction of 10% is prepared, and the hindered phenol / epoxy microspheres are dispersed in the acid solution to obtain dispersion A, and the mass ratio of hindered phenol / epoxy microspheres to the acid solution is 1:20, and the mixture is stirred at 32°C for 52 minutes, filtered, washed, and dried at 58°C for 16 hours to obtain surface acid-etched hindered phenol / epoxy microspheres; S2: Acetic acid and deionized water are mixed at a mass ratio of 1:20 to obtain an acetic acid solution, and then chitosan is added at a feed rate of 5 g / L, and the chitosan solution is obtained by stirring. Nano-silicon dioxide is added to the chitosan solution at a mass ratio of 5% to obtain a dispersion B, and the dispersion is reacted for 2 hours, filtered, washed, and dried at 58°C for 1.2 hours to obtain modified nano-silicon dioxide; aqueous polyurethane is dissolved in NN dimethylformamide, wherein the aqueous polyurethane accounts for 12% of the mass of NN dimethylformamide, and stirred at 20°C for 2 hours to obtain a polyurethane solution; ethylenediamine is dissolved in anhydrous ethanol to obtain an ethylenediamine solution, wherein the ethylenediamine accounts for 5% of the mass of the aqueous polyurethane, and the solution is added to the polyurethane solution and stirred to obtain a reaction solution. The reaction solution is placed in a reflux device and reacted at 90°C for 2 hours, and then naturally cooled and added to anhydrous ethanol accounting for 1% of the mass of the polyurethane. % modified nano-silica to obtain a mixed solution B, ultrasonically treat at a power of 200 W for 30 min, and stir at a constant temperature of 74°C for 1.3 h to obtain a mixed solution C, add deionized water to the mixed solution C, filter, wash, and dry to obtain a modified polyurethane, wherein the drying temperature is 57°C and the time is 15 h; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water and stir. Add mica powder, talcum powder and additives during the stirring process and stir evenly to obtain a water-based damping coating.
[0069] The infrared spectra of modified polyurethane with and without surface acid-etched hindered phenol / epoxy microspheres are shown in Figure 2. Figure 2 As shown: The stretching vibration peak of the NH bond in the urethane group of polyurethane is located at 3384 cm -1After adding hindered phenol / epoxy microspheres into polyurethane, the characteristic peak of NH bond shifted to 3351 cm -1 This indicates that the hydrogen bond density between the NH bonds on the microsphere surface and the antioxidant AO-80 increases.
[0070] Example 2 This embodiment provides a water-based damping coating and a preparation method thereof, wherein the water-based damping coating comprises the following components in parts by weight: 50 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 12 parts; 15 parts of filler; 10 parts of additives.
[0071] like Figure 1 As shown, the preparation method of the water-based damping coating specifically includes the following steps: S1: Emulsifier OP-10 and montmorillonite are dispersed in deionized water, wherein the mass ratio of emulsifier OP-10 to deionized water is 1:23, and the mass ratio of montmorillonite to deionized water is 1:23, and stirred at a temperature of 65°C and a rotation speed of 1100 rpm for 2 hours to obtain emulsion A; bisphenol A diglycidyl ether and antioxidant AO-80 are mixed at a mass ratio of 3:1, and stirred at 122°C for 1.6 hours to obtain a mixed solution A, and the mixed solution A is slowly dripped into the emulsion A at a dropping speed of 1.5 g / min, and stirred at a temperature of 75°C and a rotation speed of 1150 rpm for 1 hour to obtain emulsion B , wherein the mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in emulsion B is 1:1.5, then 3g of m-phenylenediamine is added to emulsion B, and after curing at 80°C for 3h, it is filtered, washed, and dried to obtain hindered phenol / epoxy microspheres, wherein the drying temperature is 52°C and the time is 5.4h; a sulfuric acid solution with a volume fraction of 12% is prepared, and the hindered phenol / epoxy microspheres are dispersed in the acid solution to obtain dispersion A, and the mass ratio of hindered phenol / epoxy microspheres to the acid solution is 1:17, stirred at 25°C for 60min, filtered, washed, and dried at 50°C for 24h to obtain surface acid-etched hindered phenol / epoxy microspheres; S2: Acetic acid and deionized water were mixed at a mass ratio of 1:17 to obtain an acetic acid solution, and then chitosan was added at a feed rate of 8 g / L, and the mixture was stirred to obtain a chitosan solution. Nano-calcium carbonate was added to the chitosan solution at a mass ratio of 4% of the chitosan solution to obtain a dispersion B, and the mixture was reacted for 1.2 h, filtered, washed, and dried at 52°C for 1.7 h to obtain modified nano-calcium carbonate; aqueous polyurethane was dissolved in NN dimethylformamide, the aqueous polyurethane accounted for 17% of the mass of NN dimethylformamide, and stirred at 23°C for 1.6 h to obtain a polyurethane solution; diethylenetriamine was dissolved in A diethylenetriamine solution is obtained in anhydrous ethanol, wherein the diethylenetriamine accounts for 15% of the mass of the waterborne polyurethane, and the diethylenetriamine solution is added to the polyurethane solution, and stirred to obtain a reaction liquid. The reaction liquid is placed in a reflux device and reacted at 80°C for 4 hours, and then naturally cooled and added with modified nano-calcium carbonate accounting for 2% of the mass of the polyurethane to obtain a mixed solution B, which is ultrasonicated at a power of 250W for 24 minutes, and stirred at a constant temperature of 60°C for 2 hours to obtain a mixed solution C, and deionized water is added to the mixed solution C, which is filtered, washed, and dried to obtain a modified polyurethane, wherein the drying temperature is 50°C and the time is 24 hours; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water, stir, add mica powder, aluminum silicate and additives during the stirring process, and stir evenly to obtain a water-based damping coating.
[0072] Example 3 This embodiment provides a water-based damping coating and a preparation method thereof, wherein the water-based damping coating comprises the following components in parts by weight: 70 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 18 parts; 5 parts of filler; 2 parts of additives.
[0073] like Figure 1 As shown, the preparation method of the water-based damping coating specifically includes the following steps: S1: Emulsifier OP-10 and montmorillonite were dispersed in deionized water, wherein the mass ratio of emulsifier OP-10 to deionized water was 1:15, and the mass ratio of montmorillonite to deionized water was 1:30, and stirred at a temperature of 72°C and a rotation speed of 1500 rpm for 1.2 h to obtain emulsion A; bisphenol A diglycidyl ether and antioxidant AO-80 were mixed at a mass ratio of 5:1, and stirred at 128°C for 1.2 h to obtain a mixed solution A, and the mixed solution A was slowly dripped into the emulsion A at a dropping speed of 2 g / min, and stirred at a temperature of 73°C and a rotation speed of 1000 rpm for 1.3 h to obtain emulsion B, wherein the mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in emulsion B is 1:1.8, then 5 g of m-phenylenediamine is added to emulsion B, and after curing at 72°C for 3.4 hours, the hindered phenol / epoxy microspheres are filtered, washed, and dried to obtain hindered phenol / epoxy microspheres, wherein the drying temperature is 58°C and the drying time is 4.6 hours; a nitric acid solution with a volume fraction of 18% is prepared, and the hindered phenol / epoxy microspheres are dispersed in the acid solution to obtain dispersion A, and the mass ratio of hindered phenol / epoxy microspheres to the acid solution is 1:12, and the mixture is stirred at 35°C for 36 minutes, filtered, washed, and dried at 52°C for 20 hours to obtain surface acid-etched hindered phenol / epoxy microspheres; S2: Acetic acid and deionized water were mixed at a mass ratio of 1:10 to obtain an acetic acid solution, and then chitosan was added at a feed amount of 13 g / L, and the chitosan solution was obtained by stirring. Nanographene was added to the chitosan solution at a mass of 2.5% of the chitosan solution to obtain dispersion B, and the mixture was reacted for 1.6 hours, filtered, washed, and dried at 50°C for 2 hours to obtain modified nanographene; aqueous polyurethane was dissolved in NN dimethylformamide, the aqueous polyurethane accounted for 10% of the mass of NN dimethylformamide, and stirred at 27°C for 1.4 hours to obtain a polyurethane solution; hexamethylenediamine was dissolved in anhydrous ethanol, to obtain a hexamethylenediamine solution, wherein the hexamethylenediamine accounts for 20% of the mass of the waterborne polyurethane, add the hexamethylenediamine solution to the polyurethane solution, stir to obtain a reaction solution, place the reaction solution in a reflux device, react at 83°C for 3.5 hours, cool it naturally, and then add modified nanographene accounting for 4% of the mass of the polyurethane to obtain a mixed solution B, ultrasonicate at a power of 300 W for 10 minutes, and stir at a constant temperature of 68°C for 1.7 hours to obtain a mixed solution C, add deionized water to the mixed solution C, filter, wash, and dry to obtain a modified polyurethane, wherein the drying temperature is 60°C and the time is 12 hours; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water, stir, add talcum powder, aluminum silicate and additives during the stirring process, and stir evenly to obtain a water-based damping coating.
[0074] Example 4 This embodiment provides a water-based damping coating and a preparation method thereof, wherein the water-based damping coating comprises the following components in parts by weight: 64 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 20 parts; 12 parts of filler; 7 parts of additives.
[0075] like Figure 1 As shown, the preparation method of the water-based damping coating specifically includes the following steps: S1: Emulsifier OP-10 and montmorillonite were dispersed in deionized water, wherein the mass ratio of emulsifier OP-10 to deionized water was 1:18, and the mass ratio of montmorillonite to deionized water was 1:28, and stirred at a temperature of 67°C and a rotation speed of 1350 rpm for 1.6 h to obtain emulsion A; bisphenol A diglycidyl ether and antioxidant AO-80 were mixed at a mass ratio of 2:1, and stirred at 130°C for 1 h to obtain a mixed solution A, and the mixed solution A was slowly dripped into the emulsion A at a dropping speed of 3 g / min, and stirred at a temperature of 67°C and a rotation speed of 1450 rpm for 1.7 h to obtain emulsion B , wherein the mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in emulsion B is 1:2, then 4.6g of m-phenylenediamine is added to emulsion B, and after curing at 78°C for 3.8h, filtered, washed, and dried to obtain hindered phenol / epoxy microspheres, wherein the drying temperature is 50°C and the time is 6h; a nitric acid solution with a volume fraction of 20% is prepared, and the hindered phenol / epoxy microspheres are dispersed in the acid solution to obtain dispersion A, the mass ratio of hindered phenol / epoxy microspheres to the acid solution is 1:10, stirred at 28°C for 30min, filtered, washed, and dried at 60°C for 12h to obtain surface acid-etched hindered phenol / epoxy microspheres; S2: Acetic acid and deionized water were mixed at a mass ratio of 1:12 to obtain an acetic acid solution, and then chitosan was added at a feed amount of 15 g / L, and the chitosan solution was obtained by stirring. Nano-silica was added to the chitosan solution at a mass of 1% of the chitosan solution to obtain a dispersion B, and the mixture was reacted for 1 hour, filtered, washed, and dried at 60°C for 1 hour to obtain modified nano-silica; aqueous polyurethane was dissolved in NN dimethylformamide, the aqueous polyurethane accounted for 20% of the mass of NN dimethylformamide, and stirred at 30°C for 1 hour to obtain a polyurethane solution; ethylenediamine was dissolved in water; In water and ethanol, an ethylenediamine solution is obtained, wherein the ethylenediamine accounts for 8% of the mass of the waterborne polyurethane, and the ethylenediamine solution is added to the polyurethane solution, and stirred to obtain a reaction liquid, and the reaction liquid is placed in a reflux device to react at 88°C for 2.2 hours, and then naturally cooled, and then modified nano-silica accounting for 5% of the mass of the polyurethane is added to obtain a mixed solution B, which is ultrasonicated at a power of 280W for 12 minutes, and stirred at a constant temperature of 80°C for 1 hour to obtain a mixed solution C, and deionized water is added to the mixed solution C, which is filtered, washed, and dried to obtain a modified polyurethane, wherein the drying temperature is 53°C and the time is 20 hours; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water and stir. Add mica powder, talcum powder, aluminum silicate and additives during the stirring process and stir evenly to obtain a water-based damping coating.
[0076] Comparative Example 1 This embodiment provides a water-based damping coating, which is different from Example 1 in that the mass fraction of surface-etched hindered phenol / epoxy microspheres in the water-based damping coating is adjusted to 30 parts. Compared with Example 1, the mass fraction of surface-etched hindered phenol / epoxy microspheres in this embodiment is increased by 20 parts, and the increased mass fraction is deducted from the modified polyurethane, filler, and auxiliary agent in proportion, so that the mass fraction ratios of other components except surface-etched hindered phenol / epoxy microspheres remain unchanged. The mass fractions of the components of the adjusted water-based damping coating are as follows: 38.82 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 30 parts; Filler 5.65 parts; 3.53 parts of additives.
[0077] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0078] Comparative Example 2 This embodiment provides a water-based damping coating, which differs from Embodiment 1 in that the mass fraction of surface-etched hindered phenol / epoxy microspheres in the water-based damping coating is adjusted to 5 parts. Compared with Embodiment 1, the mass fraction of surface-etched hindered phenol / epoxy microspheres in this embodiment is reduced by 5 parts, and the reduced mass fraction is added to the mass fraction of modified polyurethane, filler, and auxiliary agent in equal proportion, so that the mass fraction ratios of other components except surface-etched hindered phenol / epoxy microspheres remain unchanged. The mass fractions of the components of the adjusted water-based damping coating are as follows: 59.04 parts of modified polyurethane; Surface acid-etched hindered phenol / epoxy microspheres 5 parts; Filler 8.59 parts; 5.37 parts of additives.
[0079] The other process parameters and operating conditions are exactly the same as those in Example 1.
[0080] The performance test of the water-based damping coatings of the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 is carried out, and the specific process is as follows: The functional groups in the molecular structure of the modified polyurethane with and without the addition of surface acid-etched hindered phenol / epoxy microspheres in Example 1 were characterized using Fourier transform infrared spectrometer.
[0081] The composite loss factors of the water-based damping coatings of Examples 1 to 4 and Comparative Examples 1 to 2 were tested in a temperature range of -40°C to 50°C, and the test method was based on GB / T16406-1996.
[0082] Figure 3 is a composite loss coefficient curve of the water-based damping coating of Example 1-Example 4 and Comparative Example 1-Comparative Example 2, Figure 3 As shown, a high loss coefficient means that the material can effectively absorb vibration energy and reduce the propagation and amplitude of vibration. Therefore, the higher the composite loss coefficient, the better the damping performance of the material. That is, the water-based damping coatings of Examples 1 to 4 have good damping performance.
[0083] It can be seen from the test results of Example 1 and Comparative Examples 1 and 2 that an appropriate amount of hindered phenol / epoxy microspheres can significantly improve the damping performance of the coating. When the mass fraction of surface acid-etched hindered phenol / epoxy microspheres in the water-based damping coating is too much, agglomeration may occur between the microspheres, resulting in weakened interfacial interaction, reduced microsphere dispersion effect, and thus weakened damping performance; at the same time, too high a microsphere content may lead to increased material rigidity, reduced flexibility and internal friction of the coating, which is not conducive to the damping performance.
[0084] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a water-based damping coating, characterized in that: The preparation method is: S1: dispersing emulsifier OP-10 and montmorillonite in deionized water, stirring at a constant temperature to obtain emulsion A; mixing bisphenol A diglycidyl ether and antioxidant AO-80, stirring to obtain a mixed solution A, slowly dropping the mixed solution A into emulsion A, stirring at a constant temperature to obtain emulsion B, then adding meta-xylylenediamine into emulsion B, filtering after solidification, washing, and drying to obtain hindered phenol / epoxy microspheres; An acid solution is prepared, and the hindered phenol / epoxy microspheres are dispersed in the acid solution to obtain a dispersion A, and the dispersion A is stirred, filtered, washed, and dried to obtain surface-acid-etched hindered phenol / epoxy microspheres; S2: mixing acetic acid and deionized water to obtain an acetic acid solution, then adding chitosan, stirring to obtain a chitosan solution, adding the nanomaterial to the chitosan solution to obtain a dispersion B, reacting, filtering, washing and drying to obtain a modified nanomaterial; Dissolving aqueous polyurethane in NN dimethylformamide and stirring to obtain a polyurethane solution; dissolving an amine compound in anhydrous ethanol to obtain an amine compound solution, adding the amine compound solution to the polyurethane solution and stirring to obtain a reaction solution, placing the reaction solution in a reflux device for reaction, cooling it naturally, and then adding a modified nanomaterial to obtain a mixed solution B, ultrasonicating it, stirring it at a constant temperature to obtain a mixed solution C, adding deionized water to the mixed solution C, filtering, washing, and drying to obtain a modified polyurethane; S3: Dissolve the modified polyurethane and the surface acid-etched hindered phenol / epoxy microspheres in deionized water, stir, add fillers and additives during the stirring process, and stir evenly to obtain a water-based damping coating.
2. The method for preparing a water-based damping coating according to claim 1, characterized in that: The mass ratio of the emulsifier OP-10 to deionized water is 1: (15-25); The mass ratio of the montmorillonite to deionized water is 1: (20-30); The stirring temperature of the emulsion A is 65-75°C; The stirring time of the emulsion A is 1 to 2 hours; The stirring speed of the emulsion A is 1000-1500 rpm; The mass ratio of bisphenol A diglycidyl ether to antioxidant AO-80 is (1-5):1; The stirring temperature of the mixed solution A is 120-130°C; The stirring time of the mixed solution A is 1 to 2 hours.
3. The method for preparing a water-based damping coating according to claim 1, characterized in that: When the mixed solution A is added dropwise to the emulsion A, the dropping speed is 1-3 g / min; The mass ratio of emulsifier OP-10 to bisphenol A diglycidyl ether in the emulsion B is 1:(1-2); The stirring temperature of the emulsion B is 65-75°C; The stirring time of the emulsion B is 1 to 2 hours; The stirring speed of the emulsion B is 1000-1500 rpm; The feeding amount of the meta-xylylenediamine is 2-5 g; The curing temperature of the emulsion B is 70-80°C; The curing time of the emulsion B is 3 to 4 hours; The hindered phenol / epoxy microspheres are dried at a temperature of 50-60°C; The hindered phenol / epoxy microspheres are dried for 4 to 6 hours.
4. The method for preparing a water-based damping coating according to claim 1, characterized in that: The acid in the acid solution is nitric acid or sulfuric acid; The volume fraction of acid in the acid solution is 10-20%; The mass ratio of the hindered phenol / epoxy microspheres to the acid solution is 1:(10-20); The stirring temperature of the dispersion A is 25-35°C; The stirring time of the dispersion A is 30 to 60 minutes; The drying temperature of the surface acid-etched hindered phenol / epoxy microspheres is 50-60°C; The surface acid-etched hindered phenol / epoxy microspheres are dried for 12 to 24 hours.
5. The method for preparing a water-based damping coating according to claim 1, characterized in that: The mass ratio of the acetic acid to the deionized water is 1:(10-20); The feeding amount of the chitosan is 5-15 g / L; The nano material is any one of nano silicon dioxide, nano calcium carbonate, and nano graphene; The nanomaterial accounts for 1-5% of the mass of the chitosan solution; The reaction time of the dispersion B is 1 to 2 hours; The drying temperature of the modified nanomaterial is 50-60°C; The modified nanomaterial drying time is 1 to 2 hours.
6. The method for preparing a water-based damping coating according to claim 1, characterized in that: The waterborne polyurethane accounts for 10-20% of the mass of NN dimethylformamide; The stirring temperature of the polyurethane solution is 20-30°C; The polyurethane solution is stirred for 1 to 2 hours; The amine compound is any one of ethylenediamine, diethylenetriamine, and hexamethylenediamine; The amine compound accounts for 5-20% of the mass of the polyurethane; The reaction temperature of the reaction liquid in the reflux device is 80-90°C; The reaction time of the reaction solution in the reflux device is 2 to 4 hours.
7. The method for preparing a water-based damping coating according to claim 1, characterized in that: The modified nanomaterial accounts for 1-5% of the mass of the polyurethane; The power of the ultrasound of the mixed solution B is 200-300W; The ultrasonic time of the mixed solution B is 10 to 30 minutes; The stirring temperature of the mixed solution B is 60-80°C; The stirring time of the mixed solution B is 1 to 2 hours; The drying temperature of the modified polyurethane is 50-60°C; The modified polyurethane is dried for 12 to 24 hours.
8. A water-based damping coating is prepared by the method for preparing a water-based damping coating according to any one of claims 1 to 7, characterized in that: The water-based damping coating comprises the following components in parts by weight: 50-70 parts of modified polyurethane, 10-20 parts of surface acid-etched hindered phenol / epoxy microspheres, 5-15 parts of fillers, and 2-10 parts of additives.
9. The water-based damping coating according to claim 8, characterized in that: The filler includes one of mica powder, talc powder, aluminum silicate or a combination of any two of them.
10. The water-based damping coating according to claim 8, characterized in that: The auxiliary agents include plasticizers, defoamers, preservatives and anti-settling agents; The mass of the plasticizer accounts for 1-5% of the total mass of the water-based damping coating; the mass of the defoamer accounts for 0.1-1% of the total mass of the water-based damping coating; the mass of the preservative accounts for 0.1-0.5% of the total mass of the water-based damping coating; the mass of the anti-settling agent accounts for 0.5-2% of the total mass of the water-based damping coating.
Citation Information
Patent Citations
Silicon dioxide loaded chitosan modified waterborne polyurethane acrylate composite emulsion, preparation method therefor and application of composite emulsion
CN110591543A
Water-based damping coating with heat insulation, vibration reduction and noise reduction effects
CN111471393A
Ag-TiO2 modified polyurethane antibacterial coating and preparation method thereof
CN111704852A
Application of modified chitosan in coating
CN114106643A
Anticorrosive flame-retardant waterborne polyurethane as well as preparation method and application thereof
CN115678406A
Cited By
Porous ceramic sound insulation board and preparation method thereof
CN121292992A
